KARAKTERISTIK KOMBUCHA KULIT BUAH KOPI ARABIKA (Coffea arabica L.) DENGAN BERBAGAI VARIAN RASA - Base, Nurul Hidayah; N Noena, Raymond Arief (Akademi Farmasi Yamasi Makassar, 2024)
Arabica coffee fruit skin (Cofea arabica L.) known as cascara is coffee waste which contains polyphenolic compounds which are antioxidants, which can be processed into processed products that are healthy for health, such as kombucha drinks as a result of fermentation from the symbiotic Scooby culture. This research aims to determine how to make and characterize the physical quality of Arabica coffee fruit skin kombucha with various flavor variants. This research is an experimental laboratory research by making kombucha tea from Arabica coffee fruit skin powder which is brewed in hot water, stored for 14 days. Adding sugar and Scoby, then physical quality characterization was carried out after being given flavor variants, namely original (F1), Strawberry (F2), Lemon (F3), Ginger (4) and Cinnamon (5). Kombucha tea Arabica coffee fruit skin has organoleptic characteristics with yellow (F1, F3, F4), red (F2), brownish yellow (F5); The distinctive aroma of each formula corresponds to the aroma of the additional ingredients provided; Sour taste (F1, F3, F4), slightly sweet sour (F2), sweet (F5). pH 3-4 and alcohol content of 0.3% (F1) and 0% (F2, F3, F4, F5). Kombucha tea made from Arabica coffee fruit skin has typical organoleptic characteristics, pH < 4.5 and alcohol content < 0.5%.